Rheopheresis for Digital Ulcers and Raynaud's Phenomenon in Systemic Sclerosis Refractory to Conventional Treatments - Korsten, Peter; Müller, Gerhard A.; Rademacher, Jan-Gerd; Zeisberg, Michael; Tampe, Björn (Frontiers in Medicine, 2019)
Raynaud’s phenomenon (RP) is almost universally present in patients with Systemic Sclerosis (SSc). RP represents a generalized vasculopathy and potentially lead to digital ulcers (DU), which may be complicated by superinfection, tissue necrosis, and limb loss. We report the analysis of an extracorporeal procedure in a 36-year-old female patient with diffuse SSc with refractory RP and DU despite treatment with diltiazem, candesartan, sildenafil, and intravenous iloprost. We performed rheopheresis (RheoP), a variant of double-filtration plasmapheresis, as a potential new treatment option for refractory patients despite optimal medical therapy. We performed two RheoP per week every four weeks for a total of three months. Clinical improvement in DU healing occurred with no adverse events directly related to the treatment. While there was no reduction in the number of Raynaud attacks with RheoP, a significant reduction of the duration of attacks from a median of 15 (5-45, 95% CI 10-15) to 7 (3-30, 95% CI 6-10) minutes with an improvement of the Raynaud Condition Score (RCS) improved from 4 to 2. In conclusion, RheoP is a feasible and potentially beneficial treatment modality in patients with refractory RP and DU. We propose that RheoP should be investigated in a larger number of patients in a clinical trial setting.